2018
DOI: 10.1590/s2175-97902017000300252
|View full text |Cite
|
Sign up to set email alerts
|

Use of unlicensed and off-label drugs in neonates in a Brazilian university hospital

Abstract: This study was designed to investigate the use of off-label and unlicensed drugs in a Neonatal Care Unit (NCU) and to compare the frequency of use of off-label drugs according to the drug regulatory agencies in Brazil (Agência Nacional de Vigilância Sanitária-ANVISA) and the United States Food and Drug Administration (FDA). A prospective observational study was carried out in the NCU. Prescriptions were classified as off-label and unlicensed using both ANVISA and FDA criteria. A total of 157 newborns and 1187 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
3
12

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 30 publications
(53 reference statements)
0
12
3
12
Order By: Relevance
“…Accordingly, the overall off-label medicine use in ACSH NICU was found to be 67.58%. This was higher compared to several study findings elsewhere in the globe which reported off-label medicine use in the range of 23 to 62% [3,4,9,11,13,14,[20][21][22][23]. However, it was slightly lower compared to a study from India which reported an off-label prescription of 70% [2].…”
Section: Discussioncontrasting
confidence: 75%
See 4 more Smart Citations
“…Accordingly, the overall off-label medicine use in ACSH NICU was found to be 67.58%. This was higher compared to several study findings elsewhere in the globe which reported off-label medicine use in the range of 23 to 62% [3,4,9,11,13,14,[20][21][22][23]. However, it was slightly lower compared to a study from India which reported an off-label prescription of 70% [2].…”
Section: Discussioncontrasting
confidence: 75%
“…Of the total (364) prescribed medicines only 23.63% of them were unlicensed for neonatal use. This is higher compared to reports of many studies conducted elsewhere which reported unlicensed medicine use in the range of 1.9-19% [3,11,13,22,23]. However, lower compared to a study done in India in which 56% of the prescriptions were unlicensed for neonatal use [4].…”
Section: Discussioncontrasting
confidence: 59%
See 3 more Smart Citations